2016
DOI: 10.1017/s0373463315001101
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis for BDS Phase-smoothed Pseudorange Differential Positioning

Abstract: The positioning accuracy of the BeiDou Navigation Satellite System (BDS) can reach up to 10 m (95% confidence level) in both horizontal and vertical components. In order to improve the positioning performance for metre-level navigation, BDS pseudorange differential positioning has been proposed. We introduce the basic principles of BDS pseudorange differential positioning. Then based on the traditional Hatch filter, a modified Hatch filter for dual-frequency phase-smoothed pseudorange is introduced. The phase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…Subtracting the nominal IF (3·563 MHz) from the NCO frequency, we get the Doppler measurements, and these Doppler measurements do not fluctuate around zero. One of the outputs of the PLL is the integrated Doppler, which can be used in carrier phase- or Doppler-smoothed code pseudorange applications (Bahrami and Ziebart, 2011; Tang et al, 2016). The integrated Doppler d ϕ k at epoch k is calculated as: where f d ( t ) is the Doppler measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Subtracting the nominal IF (3·563 MHz) from the NCO frequency, we get the Doppler measurements, and these Doppler measurements do not fluctuate around zero. One of the outputs of the PLL is the integrated Doppler, which can be used in carrier phase- or Doppler-smoothed code pseudorange applications (Bahrami and Ziebart, 2011; Tang et al, 2016). The integrated Doppler d ϕ k at epoch k is calculated as: where f d ( t ) is the Doppler measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Here the pseudorange correction from one reference station b to one satellite q can be expressed as [8] PRC…”
Section: Differential Corrections Estimationmentioning
confidence: 99%
“…Li et al [6] and Zhou et al [7] have demonstrated the good performance of GPS + BDS real-time differential positioning for short baselines. However, the positioning accuracy and reliability deteriorates as the baseline length gets longer because of the reduced spatial correlation of several distance-dependent errors [8]. Thanks to the infrastructure of multiple reference stations, the network real-time differential positioning can provide a potential solution.…”
Section: Introductionmentioning
confidence: 99%
“…Fully exploiting the advantages of pseudorange and carrier phase while avoiding their disadvantages is naturally the best choice to improve positioning performance, which is apparently a data fusion problem. Many scholars have proposed a variety of carrier phase smoothing pseudorange algorithms [2][3][4][5]. However, the steady accuracy of carrier phase smoothing pseudorange is still worth studying theoretically.…”
mentioning
confidence: 99%
“…N k refers to the integer ambiguity corresponding to its carrier wavelength l. T k , I k and z k represent tropospheric delay, ionospheric delay and other un-modeled error terms, respectively. By subtracting (1) and (2) between k and k−1 epoch, the integer ambiguity can be eliminated as shown in the following equations:…”
mentioning
confidence: 99%